Analisis kontribusi motivasi belajar terhadap prestasi belajar siswa SMP/MTs Provinsi Banten - Putri Zuliyanti; Nugraha Wirawan; Ipat Apipah; Endah Isnaintri (Universitas Sultan Ageng Tirtayasa, 2022)
The research objective is to describe the contribution of learning motivation to student achievement. Learning motivation is grouped into four domains, namely the urge to achieve something, commitment, initiative, and optimism. This research is a survey research. Research data was collected through a questionnaire, while secondary data was in the form of the results of the first and second daily assessments (PH 1 and PH 2) as well as the results of the midterm assessment (PTS) for the 2022/2023 school year. The study population was junior high school students in Banten province with a sample of 200 class VIII in Pandeglang, Cilegon and Tangerang regencies. The sample is determined by stratified sampling. Partial Least Square Structural Equation Modeling (PLS-SEM) analysis is used to determine the relationship between learning motivation and learning achievement. The results of the study it was found that: (1) learning motivation can explain student learning achievement by 38.5%, (2) there is a positive and significant contribution between initiative and optimism on student learning achievement with a predictive value of 0.850 and 0.829 respectively, and (3) drive to achieve something and commitment do not significantly influence student achievement with predictive values of 0.815 and 0.615 respectively.